Immunohistochemical analysis of matrix metalloproteinase-13 in human caries dentin - C. Loreto; C. Galanti; G. Musumeci; M. C. Rusu; R. Leonardi (European Journal of Histochemistry, 2014)
The immunoexpression profile of matrix metalloproteinase-13 was investigated for the first time in dentin of human caries and healthy teeth. Twelve permanent premolars (10 caries and 2 sound) were decalcified in ethylenediaminetetraacetic acid and processed for embedding in paraffin wax. Sections 3-4 µm in thickness were cut and processed for immunohistochemistry. A mouse monoclonal anti-metalloproteinase-13 antibody was used for localisation using an immunoperoxidase technique. Dentinal immunoreactivity was detected in all teeth; it was weak in sound teeth and strong close to the caries area. These in vivo findings suggest a role for metalloproteinase-13 in the development and progression of adult human dental tissue disorders.